Analysis of Variation in Basic Chemistry Semester Learning Plans in Indonesian Universities: Learning Achievements, Learning Methods, and Evaluation - Desi Aryanti Nabuasa; Wiji; Wahyu Sopandi (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the variations in the preparation of Semester Learning Plans (SLP) for the Basic Chemistry 1 course across 19 chemistry education programs at 31 universities in Indonesia. The study focuses on key aspects such as material coverage, learning methods, evaluation techniques, book references, and learning media used in each SLP. Using a qualitative descriptive approach and content analysis of 19 SLP documents, the study reveals significant diversity in the covered topics, teaching methods, and evaluation techniques employed across institutions. Core topics like stoichiometry and atomic structure are taught universally, but there is notable variation in specialized content such as green chemistry, air pollution, and tropical rainforests. The learning methods are primarily interactive, with group discussions and project-based learning being the most dominant. However, no program explicitly integrates the scientific method into its curriculum. Evaluation techniques vary, with most programs combining written exams and practical projects. This research concludes that the variations in SLP reflect institutional efforts to align curricula with local needs and global trends. It recommends expanding the sample scope in future studies and including qualitative data such as interviews with lecturers and student surveys for a more comprehensive understanding of how SLP impacts learning outcomes.